Intangible Investments and International Business Cycles - Guido Baldi; André Bodmer (International Economics and Economic Policy, 2017)
Intangible capital is an increasingly important factor of production in advanced economies. Governments in Europe and elsewhere promote investment in intangible assets. However, the potential role of intangibles for business cycles and the international transmission of shocks is not well understood. In this paper, we investigate the international business cycle effects of intangible capital. To this aim, we build an otherwise standard two-country real business cycle model augmented by a production sector for intangibles and allow for the non-rivalrous use of intangible capital in the production of final output goods and new intangibles. We find that a model including intangibles is associated with international co-movement of tangible investment, which is a feature observed in the data that many models fail to produce.
Keywords: 330; International Business Cycles; Investment; Intangible Capital